2021
DOI: 10.1016/j.chembiol.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

N-Thio-β-lactams targeting L,D-transpeptidase-2, with activity against drug-resistant strains of Mycobacterium tuberculosis

Abstract: Highlights d Novel N-thio-b-lactams were designed and characterized on L,D-transpeptidase-2 d Five compounds present kinetic binding constants equal or superior to carbapenems d Mass spectrometry and 5 X-ray structures revealed an unusual mode of adduct formation d Growth inhibition in the mg/mL range in vitro against Mtb, including MDR isolates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…We leveraged precedents on M. tuberculosis l,d -transpeptidases and carbapenems/penems guided by crystal structures ( 52 , 53 , 57 62 ) to develop improved inhibitors of M. tuberculosis l,d -transpeptidases with the hypothesis that unique penems may exhibit improved potency against this microbe. Similar attempts at developing unique and potent inhibitors of l,d -transpeptidases using the β-lactam core have been reported independently ( 63 65 ). While a select few new penems exhibited desirable MICs against M. tuberculosis , we were gratified to find that one of these penems, T405, had MICs lower than those of imipenem and faropenem against a collection of Mab isolates ( 33 ).…”
Section: Discussionmentioning
confidence: 60%
“…We leveraged precedents on M. tuberculosis l,d -transpeptidases and carbapenems/penems guided by crystal structures ( 52 , 53 , 57 62 ) to develop improved inhibitors of M. tuberculosis l,d -transpeptidases with the hypothesis that unique penems may exhibit improved potency against this microbe. Similar attempts at developing unique and potent inhibitors of l,d -transpeptidases using the β-lactam core have been reported independently ( 63 65 ). While a select few new penems exhibited desirable MICs against M. tuberculosis , we were gratified to find that one of these penems, T405, had MICs lower than those of imipenem and faropenem against a collection of Mab isolates ( 33 ).…”
Section: Discussionmentioning
confidence: 60%
“…This is an especially useful approach as multidrug resistant microbes can persist in the environment and do not readily reverse even upon discontinuation of the treatment [ 104 ]. For example, N-thiol substituted monocyclic β-lactams covalently inhibits abundant L-D transpeptidase 2 which performs 3,3-diaminopimelic acid crosslinks in peptidoglycan of Mycobacterium tuberculosis thereby being effective against dormant and multidrug resistant isolates [ 105 ]. It has also been observed that the frequency of horizontal plasmid transfer increases in the presence of subinhibitory concentrations of antibiotics [ 106 ].…”
Section: Innovative Strategies To Overcome Antimicrobial Resistancementioning
confidence: 99%
“…It was demonstrated that the inhibition of transpeptidase Ldt Mt2 of Mycobacterium tuberculosis occurs on transfer of the thio residue from the nitrogen atom of the β-lactam to the cysteine residue of the active site of the transpeptidase, thus forming a covalent disulfide adduct with the protein, as revealed by mass spectrometry (Figure B) …”
Section: Introductionmentioning
confidence: 99%